Risk dan Return Saham Perusahaan Industri Barang Konsumsi di Bursa Efek Indonesia - Anwar Ramli (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research aims to know describe risk and return stock of Consumption Goods Industry Corporation at the Indonesian Stock Exchange. This research used documentation method to collect data. Data gets from The Center for Information Capital Market (Pusat Informasi Pasar Modal) in Makassar. The sample are 15 corporations be take from 36 corporations of Consumption Goods Industry Corporation Group in Indonesian Stock Exchange (Bursa Efek Indonesia) in the year 2008. In this research used Capital Asset Pricing Model (CAPM) for data analysis. The results of research indicate that stocks of Consumption Goods Industry Corporation have β < 1, it means that stocks have characteristic of defensive. The results of analysis also indicate that expectation return from each kind of stock accompany risk. More and more increased of β, is more also of expectation return of the stock. After analyze correlation between risk rate and return of stock from 15 samples, only five of stocks are feasible to buy, there are the stocks of Mandom Indonesia Tbk (TCID), Indofood Sukses Makmur, Tbk (INDF), Bentoel International Investama, Tbk (RMBA), HM. Sampoerna, Tbk (HMSP), and Kimia Farma, Tbk (KAEF). While 10 other stocks are not feasible to buy it, or better to sell it.Keywords: Risk and Return of Stock